Rabbi Joseph B. Soloveitchik's endorsement and critique of Volkish thought - Herskowitz, D (Taylor and Francis (Routledge), 2015)
In this article I trace and examine volkish elements in Rabbi Joseph B. Soloveitchik's thought. My claim is that Soloveitchik is influenced by different notions of volkish ideology which are applied to the Jewish volk. These notions enrich his thought and provide a language to articulate different ideas concerning Jewish peoplehood in modernity. Yet Soloveitchik was also critical of the ethical problems volkish ideology engenders—a critique that is exemplified in his reaction to the philosophy of Martin Heidegger. Soloveitchik thus adopts volkish notions and employs them in a Jewish context yet is simultaneously critical of this vein of thought and its ethical ramifications. This apparent disparity is explained through an understanding of the connection between reason and ethics in Soloveitchik's thought.